2020
DOI: 10.1242/jcs.237917
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial–nuclear heme trafficking in budding yeast is regulated by GTPases that control mitochondrial dynamics and ER contact sites

Abstract: Heme is a cofactor and signaling molecule that is essential for much of aerobic life. All heme-dependent processes in eukaryotes require that heme is trafficked from its site of synthesis in the mitochondria to hemoproteins located throughout the cell. However, the mechanisms governing the mobilization of heme out of the mitochondria, and the spatiotemporal dynamics of these processes, are poorly understood. Here, using genetically encoded fluorescent heme sensors, we developed a livecell assay to monitor heme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 73 publications
(140 reference statements)
2
45
0
Order By: Relevance
“…Thus, the ratio of eGFP:mKATE2 fluorescence is inversely correlated with bioavailable heme, as measured by HS1. HS1 was previously used to characterize heme homeostasis in yeast, bacteria, and mammalian cells, and was instrumental in identifying new heme trafficking factors and signals that alter heme biodistribution and dynamics (40,(42)(43)(44). We asked if cytosolic heme bioavailability is altered in response to G4 ligand PhenDC3 (40).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the ratio of eGFP:mKATE2 fluorescence is inversely correlated with bioavailable heme, as measured by HS1. HS1 was previously used to characterize heme homeostasis in yeast, bacteria, and mammalian cells, and was instrumental in identifying new heme trafficking factors and signals that alter heme biodistribution and dynamics (40,(42)(43)(44). We asked if cytosolic heme bioavailability is altered in response to G4 ligand PhenDC3 (40).…”
Section: Resultsmentioning
confidence: 99%
“…By adapting previously established sensor calibration procedures to C. albicans (see Section 4), we find that the wild‐type HS1 sensor is ~80% loaded with heme, while the HS1‐M7A sensor is <10% heme loaded in synthetic complete (SC) medium. This calculation is based on the wild‐type HS1 and HS1‐M7A eGFP/mKATE2 sensor ratios compared to the non‐binding HS1 DM sensor ratio, which gives the ratio if the sensor is 0% bound on the one hand, and an eGFP/mKATE2 ratio of 0, which is the ratio when the sensor is 100% bound to heme on the other hand (since energy transfer is >99% efficient between eGFP and heme, sensor that is fully bound to heme will exhibit a eGFP/mKATE2 ratio of 0 since the eGFP fluorescence will be fully quenched) (Hanna et al, 2016; Martinez‐Guzman et al, 2020). In principle, the fractional heme occupancy of HS1 can be used to estimate the concentration of buffered LH concentrations (Hanna et al, 2016; Hanna et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…We show here that exogenously scavenged heme can in fact serve as a heme source in C. albicans and contribute to the LH pool. Ratiometric fluorescent sensors for LH were recently developed and utilised in Saccharomyces cerevisiae , E. coli and mammalian cell lines to probe heme trafficking and dynamics (Hanna et al, 2016; Hanna et al, 2018; Hanna, Martinez‐Guzman, & Reddi, 2017; Martinez‐Guzman et al, 2020; Sweeny et al, 2018). Adapting these heme sensors to C. albicans , we measured the effects of iron starvation, heme depletion and extracellular heme supplementation on intracellular heme levels.…”
Section: Introductionmentioning
confidence: 99%
“…However, compared to animals and yeast, the heme trafficking mechanism is poorly understood in plants [ 4 ]. In yeast, using a genetically encoded fluorescent heme sensor [ 128 ], it was shown that heme synthesized in the inner mitochondrial membrane can be transferred to the nucleus and the cytosol in distinct pathways [ 129 ]. Heme synthesized in the mitochondria was transferred to the nucleus via mitochondria-associated ER membrane contact sites (MCSs) that was faster than cytosolic heme transfer [ 129 ].…”
Section: Discussionmentioning
confidence: 99%